Structuring the genetic collection of sunflower - V. A. Gavrilova; I. N. Anisimova; N. V. Alpatieva; E. A. Porokhovinova (Труды по прикладной ботанике, генетике и селекции)
Background. The XRQ sunflower genome has been sequenced but not yet fully annotated, and not all candidate genes for most traits have been identified. Disclosing the relationships among traits in this study will help to understand the genetic control over phenotypic characters.Materials and methods. A set of 237 sunflower lines from VIR’s genetic collection was phenotyped for their morphological characters (plant height; branching type; shapes and sizes of the leaf, petiole, flower head, disk and ray florets; downy mildew damage rate) and genotyped with molecular markers. DNA markers were used to identify accessions carrying the Rf gene and CMS. Factor analysis was applied to structure the genetic collection.Results and discussion. The data of 2017 and 2018 were compared using the analysis of variance. The results of the latter testified to the heritability of morphological characters, as well as to the alignment and purity of lines from VIR’s genetic collection of sunflower. New data were obtained on the phenotypic diversity of sunflower and stability of its agronomic traits across the growing seasons.Conclusion. Groups of interacting characters were identified by the factor analysis: 1) plant height, and duration of the growing season phases; 2) pollen fertility restoration with CMS PET1, SCAR markers HRG02 and HRG01 of the Rf1 gene, and branching; 3) the color of ray and disk florets, and petiole shape, as well as lamina surface shape. Lines with CMS PET1 were classified into three groups differing in the systems (possibly genes) of pollen fertility restoration. The factor analysis made it possible to confirm the assumption that several Rf genes whose manifestation differed from the Rf1 gene were present in the studied sunflower lines from VIR’s genetic collection.